Peningkatan Hasil Belajar Matematika Kelas V Pada Materi Sudut Melalui Model STAD Berbantu Media Konkret JASU (Jam Sudut) - Setyawan, Syahrul Ramadani; Arsyad Fardani, Much; Hamim, Nurul (Universitas Islam Nahdlatul Ulama Jepara, 2025)
This research aims to enhance the mathematics learning outcomes of fifth-grade students at SD 2 Medini Kudus on the topic of angles through the implementation of the Student Teams Achievement Division (STAD) cooperative learning model supported by a concrete learning medium called the Angle Clock (JASU). The study employed a classroom action research design following the Kemmis and Taggart model. The research was conducted in two cycles during the even semester of the 2024/2025 academic year, involving 27 students as research participants. Each cycle included four stages: planning, implementation, observation, and reflection. Data collection was carried out using learning outcome tests and observations conducted by appointed observers. The findings revealed an improvement in students' mastery, with classical completeness rising from 55% in the first cycle to 81% in the second, accompanied by an increase in the average score from 69 to 83. These results demonstrate that the integration of the STAD learning model and JASU media positively contributes to students’ understanding of angle material. Thus, this approach is recommended as an effective alternative for teaching mathematics in elementary education.